Design of a pure rotation micropositioning stage with dual-range. (March 2022) - Zhang, Juncang; Gan, Jinqiang; Ding, Huafeng; Li, Hai
Abstract: In this paper, a pure rotation micropositioning stage with dual-range is designed to acquire a large-rotation angle and a high-resolution at the same time. The designed stage consists of a large-range rotation mechanism and a small-range rotation mechanism and it combines nested structure, multi-layer and symmetric structure. Analytical modeling is presented to investigate the kinematic and static characteristics by using the compliance matrix method and pseudo-rigid-body model. A series of simulations are conducted to demonstrate the effectiveness of the proposed design. The simulation results show that the designed stage has a large-rotation range of [0 mrad, 17.40 mrad] and a small-rotation range of [0 mrad, 0.88 mrad]. Highlights: &#x00002022; A pure rotation micropositioning stage with dual-range is designed. &#x00002022; The stage consists of a large-range and a small-range rotation mechanism. &#x00002022; The stage combines nested structure, multi-layer and symmetric structure. &#x00002022; The stage has the merits of large output angle, high resolution and compact size.